Analisis Pengaruh Kompensasi dan Motivasi Terhadap Kinerja Karyawan Apotek di Kecamatan Purwareja Klampok - Lestari, Endah; Supriatin, Dyah; Barima, Hima (Perwira Journal of Economics & Business, 2023)
The purpose of this study was to determine the partial and simultaneous effect of compensation (X1) and motivation (X2) on the performance of employees (Y) of the Pharmacy in Purwareja Klampok District. The data collection technique in this study used purposive sampling. Data collection techniques used by researchers were questionnaires and interviews using multiple regression analysis with the help of SPSS 26 to 38 respondents as a sample and the population taken was all Pharmacy employees in Purwareja Klampok District with the specified characteristics. This study uses a type of quantitative research. Based on the results of this study, the compensation variable using the T test obtained a t table of 2.030 while the t count was -1.184, the motivational variable t table was 2.030 and the t count was 8.315, then the employee performance variable using the F test obtained an f table of 3.259 with sig. 0.05 while the f count is 48.504. Then the conclusions obtained are that compensation does not affect performance, motivation influences performance, and compensation and motivation simultaneously affect employee performance. The coefficient of determination (R-Square) is 0.720, which means that 72% of employee performance variables can be explained by independent variables, the remaining 28%, which means that they are influenced by other variables not included in this study.